Co-relation between xanthine oxidase and ceruloplasmin in acute myocardial infarction - Kale, Bhagwat (International Journal of Biological Research, 2013)
Myocardial ischemia results from the reduction of coronary flow to such an extent that supply of oxygen to the myocardium does not meet the oxygen demand of myocardial tissue. Xanthine oxidoreductase, under normal conditions, exists in dehydrogenase form. Under ischemic conditions it is converted into xanthine oxidase. Ceruloplasmin is ?2 globulin –a glycoprotein, an acute phase protein synthesized by the liver in response to tissue damage. Our aim in this study was to determine levels of xanthine oxidase and ceruloplasmin in acute myocardial infarction.We found that, xanthine oxidase activity in acute myocardial infarction patients increases significantly (p < 0.01) upto 12 hours and then slowly decreases. The maximum activity is found after 12 hours of acute myocardial infarction. While, ceruloplasmin level in the serum of patients increases significantly (p < 0.01) upto 48 hours and then slowly decreases. We found xanthine oxidase and ceruloplasmin have no specific co-relation between them. But, still it is found that xanthine oxidase activity reaches to peak more early as compared to ceruloplasmin. Thus, it is concluded xanthine oxidase is more potent in diagnosis and prognosis of acute myocardial infarction and can be utilized as a marker of oxidative stress developed in acute myocardial infarction.